Digital-Efficacy Design: A Deep Learning-Based Learning Model For Literacy And Numeracy In Inclusive Schools - Yatha Yuni; Arifannisa Arifannisa; Hegar Harini (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2026)
Inclusive schools continue to strive to provide equitable education for all students, including those with disabilities. The Merdeka Curriculum emphasizes literacy and numeracy as core competencies but requires a more adaptive system to be effectively implemented in inclusive settings. This study develops and evaluates the Deep Learning-Based Digital Efficacy Design Model as an innovative approach to enhance literacy and numeracy learning for students with special needs. Using the Design and Development Research method by Richey and Klein, the research was conducted at SLBN 12 South Jakarta, involving 30 teachers and 30 students selected through cluster random sampling. Findings indicate a consistent increase in literacy and numeracy across all disability types and educational levels. These improvements demonstrate the model’s effectiveness in strengthening students’ comprehension and engagement with literacy and numeracy concepts. Additionally, the results show that the deep learning approach successfully accommodates the cognitive and sensory diversity of students, particularly those with hearing impairments and mild to moderate intellectual disabilities. Overall, the implementation of the Deep Learning-Based Digital Efficacy Design Model significantly enhanced literacy and numeracy performance in inclusive learning environments. Teachers should use adaptive digital tools and personalized feedback in daily lessons to help all students achieve literacy and numeracy